Educação patrimonial e inventário de saberes : aromas, sabores, ofícios e memórias no Mercado Central de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The purpose of this research is to carry out an inventory of knowledge and practices related to the way of preparing pies and bottles in the Central Market of Goiânia. In this sense, the focus is on the trade of holders who have exercised these trades in the market for more than 30 years. Therefore, we resorted to the Oral History approach, carried out through interviews carried out in 2023 with testimonies from 08 permit holders and 01 employee who work in the Central Market of the Capital of Goiás. Through these interviews, knowledge and memories about the history of this place that expresses the lives and memories of these workers were addressed. Furthermore, the documentary corpus is composed of written and iconographic sources linked to the market under study. Likewise, a questionnaire was administered to 70 visitors to the Central Market with the aim of understanding who the visitors are and their motivations for seeking out the market. In the field of Heritage Education, we would highlight the actions carried out with the owners through interviews that made it possible to identify the importance of safeguarding knowledge and know-how, as well as the history of the public market. Thus, the research aims to identify the crafts linked to the preparation of pies and bottles in the Central Market of Goiânia, using Oral History to discuss the bases that guide the guidelines of intangible cultural heritage. The proposed final product is a documentary video about Knowledge and Memories in the Central Market of Goiânia, created based on documentary research and testimonies from holders and, also, from those who conceive the market as a place where they carry out their trades and also a space for experiences and meanings.
Heritage education and knowledge inventory : aromas, flavors, crafts and memories in the Central Market of Goiânia
Keywords: Educação patrimonial; Memória; Saberes e fazeres; Mercado Central de Goiânia; Heritage education; Memory; Knowledge and practices; Central market of Goiânia; CIENCIAS HUMANAS::HISTORIA